13+6d=67

Simple and best practice solution for 13+6d=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13+6d=67 equation:


Simplifying
13 + 6d = 67

Solving
13 + 6d = 67

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 6d = 67 + -13

Combine like terms: 13 + -13 = 0
0 + 6d = 67 + -13
6d = 67 + -13

Combine like terms: 67 + -13 = 54
6d = 54

Divide each side by '6'.
d = 9

Simplifying
d = 9

See similar equations:

| 3(9-3x-4x)+8(3x+4)=11 | | 7(5x-4)=11(2x+1) | | 3a+4a+5=75 | | -51+2x+5x=26 | | 2=6x+1-81-y | | Solve(x-8)(3x+5)=0 | | 2y=-3x-5 | | 14=10-1/4m | | (25x-2)+(25x+1)+(20x-1)=278 | | 3(2x+2)=6(1+8x) | | (y+1)=2(x-3) | | 9c-15=4c | | 8(4x+1)=9(5x-2) | | 10x^9-17x^7+7x^6= | | 5x-1/2x=18 | | 5(x-90)-4(x+150)=950 | | x+x/2+4=30 | | 8(d+5)=23 | | 4x^2+8-12=0 | | n^2+8=-6n | | 3(7+c)=60 | | 52000-8n=18000+8n | | 8(4x+1)=14(2x-3) | | [3(m-5)+16]-[2(3m-3)+5]= | | -3+5(2x-17)=1 | | a(x-a)=1 | | 3(7+c)=51 | | w/4.3-9.8=70 | | 7-6u=5u+19 | | 4n-3n+2=5 | | 4-9x=4x+27 | | -17+6x-2x=11 |

Equations solver categories